Enamel matrix derivative in the treatment of tooth replantation: from a biological basis to clinical application - Yao Lin; Liangping Chen; Yuling Xu; Mingwei Xu; Qinghua Liu; Junbing He (Annals of Medicine)
Background An efficient therapeutic strategy for patients with replanted teeth has been extremely challenging because complete displacement of the teeth is inevitably accompanied by severe damage to periodontal tissue. Enamel matrix derivative (EMD) shows promise for periodontal regeneration, but its effects on replanted teeth remain unknown. This study systematically summarized the biological basis of EMD in replantation dental therapy and assessed its effect on clinical prognosis.Methods Potential studies were searched via the Cochrane Library, Web of Science and PubMed databases from inception to November 23, 2023.Results A total of 329 patients with 375 replanted teeth met the inclusion criteria. Our pooling results indicated that EMD did not provide a numerical advantage for restoring normal PDL healing in replanted teeth (RR=0.38, P=0.161). A significantly lower extraction risk was observed in EMD-treated group than non-EMD-treated group (RR=0.47, P=0.001). Moreover, the survival rate of replanted teeth with root resorption was significantly increased by the application of EMD (RR=2.21, P=0.017). Although the pooled outcomes suggested increased incidence of surface resorption (RR=1.19, P=0.730) and decreased risk of inflammation resorption (RR=0.68, P=0.560) among replanted teeth with resorption in the EMD-treated group, neither difference was statistically significant.Conclusion For patients with replanted teeth, EMD treatment may not result in a numerical increase in normal PDL healing. However, as a biological regulator, EMD may arrest the progression of resorption, thus reducing the risk of extraction in the early stage. Well-designed randomized trials are required to validate these results due to the poor quality of evidence.